Postoperative radiotherapy for T1/2N0M0 mucoepidermoid carcinoma positive for CRTC1/3‐MAML2 fusions. Issue 12 (26th November 2018) - Okumura, Yoshihide; Murase, Takayuki; Saida, Kosuke; Fujii, Kana; Takino, Hisashi; Masaki, Ayako; Ijichi, Kei; Shimozato, Kazuo; Tada, Yuichiro; Nibu, Ken‐ichi; Inagaki, Hiroshi
Abstract: Background: The National Comprehensive Cancer Network (NCCN) guidelines recommend considering postoperative radiotherapy (PORT) for completely resected T1/2N0M0 salivary mucoepidermoid carcinomas when they show tumor spillage, perineural invasion, or intermediate/high‐grade histology. CRTC1/3‐MAML2 fusions have been associated with a favorable clinical outcome. Methods: Forty‐seven T1/2N0M0 mucoepidermoid carcinoma cases positive for CRTC1/3‐MAML2 fusions were completely resected and were not treated with PORT. Results: Pathologically, none of the cases showed tumor spillage or perineural invasion. Cases with intermediate/high‐grade histology numbered 9 (19%) to 26 (55%) with the currently used 3 different grading systems. During the follow‐up (median 60 months), locoregional tumor recurrence occurred in 4 cases, which were treated with surgery alone. At the last follow‐up (median 60 months; 7‐160), all patients were alive with no evidence of disease. Conclusion: An excellent prognosis may be achieved without PORT in T1/2N0M0 mucoepidermoid carcinoma patients positive for CRTC1/3‐MAML2 fusions when the tumors are completely resected without tumor spillage.